Evaluation of Fire Hazard and Safety Management of Heritage Buildings in Georgetown, Penang - Othuman Mydin, M.A.; Md. Sani, N.; Abas, N.F.; Khaw, Y.Y. (EDP Sciences, 2014)
Fire is a subject that is always neglected and ignored as far as heritage buildings are concerned. Unlike newly-built buildings, which are required under UBBL to undergo certain fire protection system tests, people are less likely to carry out such tests and detailed assessments for heritage buildings. Thus, this research is significant as it is aimed at accomplishing several objectives including studying the current fire emergency plan, besides identifying and assessing the possible fire hazards in heritage buildings in Penang. Several case studies were carried out at a few premises such as the Khoo Kongsi, Cheah Kongsi, Hock Teik Chen Shin Temple and the Teochew Temple with the aid of the Fire Rescue Department Malaysia (FRDM). The results obtained from this study will be discussed according to several aspects focusing on general health and safety management at the site, the fire-fighting system, fire exit routes and signage at the temples, fire hazards, and fire detection and alarm.